Intravesical Recurrence After Radical Nephroureterectomy of Upper Urinary Tract Urothelial Carcinoma: A Large Population-Based Investigation of Clinicopathologic Characteristics and Survival Outcomes - Wu, Jie; Xu, Pei-Hang; Luo, Wen-Jie; Dai, Bo; Shen, Yi-Jun; Ye, Ding-Wei; Wang, Yu-Chen; Zhu, Yi-Ping (Frontiers in Surgery, 2021)
Background: Of patients with upper urinary tract urothelial carcinoma (UTUC), 22–47% developed bladder recurrence after radical nephroureterectomy. Furthermore, the effect of surgery for UTUC-bladder cancer (BC) has not been well validated. The aim of this study was to assess the impact of standard primary BC surgical strategy on survival of patients diagnosed with UTUC-BC. Patients and Methods: A total of 676 UTUC-BC patients and 197,753 primary BC patients diagnosed from 2004 to 2016, were identified based on the SEER database. The Kaplan-Meier method and the Fine and Gray competing risks analysis were performed to assess overall survival (OS) and cancer-specific mortality (CSM). Multivariate Cox regression model and competing risks regression model were used to identify independent risk factors. Propensity score matching (PSM) was also performed to adjust potential confounding factors. Results: The baseline characteristics and survival outcomes of the two BC patient cohorts are quite different. For UTUC-BC patients, no significant difference in OS (NMIBC: p = 0.88; MIBC: p = 0.98) or cumulative incidence of CSM (NMIBC: p = 0.12; MIBC: p = 0.96) were noted for various surgical procedures. Local tumor treatment and partial cystectomy for UTUC-NMIBC patients produced lower 1-year (6.1%) and 3-year CSM (16.2%). Radical cystectomy for UTUC-MIBC patients produced lower 1-year (11.8%) but higher 3-year CSM (62.7%). After PSM for covariates, UTUC-BC patients still had a worse prognosis after surgery compared with primary BC patients. Based on regression models, older age, advanced T stage, N positive disease, M positive disease, and shorter interval between UTUC and BC were identified as independent risk factors for UTUC-BC patients. Conclusion: Standard primary BC surgical strategy did not provide significant survival benefit for UTUC-BC patients. Compared with primary BC patients, UTUC-BC patients had a worse prognosis after surgery, suggesting that current primary BC surgical guidelines are not entirely appropriate for UTUC-BC patients. Our findings underscore the continued importance and need for better prognosis and improved guidelines for management of UTUC-BC patients.